Bovine coenurosis - Giaretta, Paula R.; Panziera, Welden; Galiza, Glauco J.N. de; Barros, Claudio S. L. (Brazilian Journal of Veterinary Pathology, 2021)
An 18-month-old mixed breed steer had incoordination, blindness, and opisthotonos for ten days. The clinical condition progressed to lethargy and lateral recumbency, and the steer was euthanized due to poor prognosis.